Law Enforcement Against Perpetrators of Assault Crimes in the Jurisdiction of Tapanuli Utara Police towards Victims Who Have Died - Habeahan, Delianto; Ismaidar; Muhammad Arif Sahlepi (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Law enforcement is the process of applying the law carried out by authorized parties in society to ensure that the law is implemented and obeyed by every citizen. This process involves security apparatus and courts that are responsible for examining and processing actions that violate the law as well as imposing sanctions on those proven guilty. Law enforcement against offenders of assault that causes the victim's death is regulated in Article 351 paragraph 3 of the Criminal Code, which addresses the crime of assault resulting in death. It states that if the act is assault that results in death, the guilty will be punished with a maximum prison sentence of 7 (seven) years. This research uses normative legal research by examining literature sources to obtain materials in the form of theories, concepts, principles, and legal regulations related to law enforcement against perpetrators of assault in the jurisdiction of the North Tapanuli Police towards victims who have died.